Waterborne anticorrosive coating for magnesium alloy and preparation method and application thereof

CN122898200APending Publication Date: 2026-10-13HUNAN SOKAN NEW MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611294185.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-25
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0009]本发明提供一种水性镁合金防腐涂料及其制备方法和应用,以解决背景技术提及的现有镁合金涂料存在的技术问题

Benefits of technology

(1)本发明的水性镁合金防腐涂料能够在镁合金金属上形成牢固附着、力学性能均衡的耐腐蚀涂层,对镁合金基材形成有效防护,采用环氧磷酸酯和磺酸盐防腐蚀剂搭配形式,利用二者的协同作用可有效增强镁合金基材的耐腐蚀性能,特别是针对长时间的高温高湿、酸性、化学品等特定环境下的耐腐蚀性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application belongs to the technical field of coating, and particularly relates to a water-based magnesium alloy anticorrosive coating, a preparation method and application thereof. The water-based magnesium alloy anticorrosive coating provided by the present application comprises component A and component B. The preparation raw material of component A comprises water-based resin, epoxy phosphate, sulfonate corrosion inhibitor, wetting agent, defoaming agent, solvent and the like. Component B comprises isocyanate curing agent and solvent. The epoxy phosphate and the sulfonate corrosion inhibitor are cooperated to form a chemical passivation layer and a physical barrier layer on the surface of the magnesium alloy, so that the long-term salt spray corrosion resistance and acid sweat corrosion resistance of the coating are significantly improved. The present application further provides a preparation method of the water-based magnesium alloy anticorrosive coating and application thereof in the corrosion prevention of magnesium alloy substrates in the field of 3C consumer electronics, and has excellent long-term corrosion resistance and good industrial application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of coating technology, specifically relating to a coating for corrosion protection of magnesium alloys, its preparation method, and its application. Background Technology

[0002] Magnesium alloys have a density approximately two-thirds that of aluminum alloys and one-quarter that of steel, making them the lightest practical metal structural material currently available. For portable laptops, tablets, smartphones, and camera bodies, using magnesium alloys directly reduces overall weight, significantly improving grip and portability. Simultaneously, its excellent specific strength and specific stiffness ensure structural robustness and pressure resistance, along with good impact resistance, while reducing weight. Magnesium alloys are extensively used in drone fuselages and gimbal components, with the core objective of reducing weight to extend flight time and improve flight control responsiveness. With the increasing adoption of smart wearable devices, magnesium alloys, due to their lightweight and high strength characteristics, are also gradually being used in various types of smart wearable devices.

[0003] However, corrosion protection of magnesium alloys has always been a technical challenge. Magnesium's standard electrode potential is only -2.37 V (relative to the standard hydrogen electrode), placing it among the lowest of all commonly used structural metals. This means that in most aqueous environments (especially humid air, chloride-containing electrolytes, or weakly acidic media), magnesium alloys have an extremely high tendency for spontaneous corrosion, making it almost impossible for them to resist corrosion based on their own thermodynamic stability. Secondly, unlike aluminum alloys, which can quickly form a dense, continuous, and self-healing alumina film, the surface film naturally formed on magnesium alloys in air is mainly composed of MgO and Mg(OH)₂. This film has a loose, porous, and brittle structure, containing numerous microcracks and defects, and cannot completely cover the metal substrate. Therefore, corrosion protection of magnesium alloys must rely on artificially intervened surface treatment techniques.

[0004] Currently, applying organic coatings to the surface of magnesium alloys (especially magnesium-aluminum alloys) is one of the commonly used anti-corrosion methods. For example, Chinese patent CN115710454B discloses a water-based two-component polyurethane coating, its preparation method, and its application. The coating of this patent exhibits excellent adhesion and good solvent resistance on magnesium-aluminum alloy plates.

[0005] However, the aforementioned existing technologies still have the following shortcomings:

[0006] First, its long-term corrosion resistance is insufficient. In the application scenarios of 3C consumer electronics, magnesium alloys inevitably come into contact with human skin. The salt and acidic substances in human sweat are highly corrosive to magnesium alloys. Over time, this can easily lead to coating failure and black spot corrosion on the surface of the magnesium alloy, seriously affecting the appearance and service life of the product.

[0007] Secondly, magnesium alloys are often treated with micro-arc oxidation (MAO). MAO treatment forms a thick oxide layer on the surface of the magnesium alloy material. This oxide layer causes the magnesium alloy material to lose its original metallic luster. If a metallic appearance is to be achieved later, it needs to be achieved through painting or vacuum plating, which increases the manufacturing cost of the workpiece. If the MAO layer is made thinner (100-150nm), the metallic texture of the magnesium alloy can be preserved as much as possible, but the material will be more susceptible to corrosion.

[0008] Therefore, developing a water-based anti-corrosion coating for magnesium alloys that can form a strong adhesion on magnesium alloy surfaces (especially magnesium alloy surfaces with a thin MAO layer), and has excellent long-term anti-corrosion performance and good film permeability is of great practical significance and application value. Summary of the Invention

[0009] This invention provides a water-based anti-corrosion coating for magnesium alloys, its preparation method, and its application, in order to solve the technical problems existing in the current magnesium alloy coatings mentioned in the background art.

[0010] The technical solution adopted in this invention includes: A water-based anti-corrosion coating for magnesium alloys, comprising component A and component B; Component A includes a resin matrix, epoxy phosphate, sulfonate corrosion inhibitor and solvent; the mass ratio of epoxy phosphate and sulfonate corrosion inhibitor is (0.8:1) to (1:1); Component B includes a curing agent.

[0011] This invention significantly improves the corrosion protection performance of magnesium alloy surfaces through the synergistic effect of epoxy phosphate and sulfonate corrosion inhibitors. Epoxy phosphate can form a passivation layer on the magnesium alloy surface, preventing external salt and moisture from corroding the magnesium alloy material. Epoxy phosphate has good initial wettability and interfacial bonding to magnesium alloys. The P=O and P-OH groups in the phosphate ester groups interact with the Mg-OH and Mg groups on the magnesium surface. 2+Hydrogen bonding, acid-base reactions, coordination, or inner-layer complexation occur at the sites, potentially forming a magnesium-phosphate type interface layer. This interfacial bridging structure—magnesium alloy / oxide film-Mg-OP-organic resin—makes the wetting interface less prone to shrinkage. Epoxy phosphate easily enters the micropores through capillary action, exhibiting a low apparent contact angle and forming mechanical interlocking and chemical bonding. This is particularly advantageous for ultrathin MAO films: epoxy phosphate can act as an adhesion promoter in primers or water-based resins, transforming MAO micropores from corrosion channels into resin anchoring points. Sulfonate corrosion inhibitors can form an umbrella-like physical barrier layer on the magnesium alloy surface. The mechanism of action includes: firstly, forming a hydrophobic barrier film through interfacial adsorption; the negatively charged sulfonic acid head groups preferentially adsorb onto the magnesium matrix and the positively charged active sites of MgO corrosion products; the long alkyl groups form an outward-facing hydrophobic layer, blocking Cl ions and water molecules from penetrating the matrix; secondly, by forming insoluble magnesium sulfonate precipitates, it blocks corrosion active sites, preventing the Mg produced by corrosion from penetrating the matrix. 2+ It reacts with adsorbed sulfonate anions to form Mg-sulfonate complex precipitates, filling surface defects and pitting initiation sites, and blocking anodic dissolution channels; furthermore, it can regulate the electric double layer, reduce corrosion current density, increase polarization resistance, shift the corrosion potential to the positive direction, and inhibit microgalvanic corrosion (between the magnesium matrix and the second phase β-Mg). 17 Al 12 (the electric couple between them).

[0012] The synergistic effect of epoxy phosphate and sulfonate corrosion inhibitors can significantly improve the long-term resistance of the coating to salt spray corrosion and acid sweat corrosion, while preserving the transparency of the paint film as much as possible, presenting the metallic texture of the magnesium alloy material.

[0013] As a further preferred embodiment of the above technical solution, the mass ratio of component A to component B is 100:(10~15). Component A comprises the following components in parts by weight: 45-75 parts water-based resin, 3-5 parts epoxy phosphate ester, 3-5 parts sulfonate corrosion inhibitor and solvent; Component B includes 70-80 parts by weight of a curing agent and a solvent, wherein the curing agent is hexamethylene diisocyanate polymer.

[0014] As a further preferred embodiment of the above technical solution, the resin matrix is ​​an aqueous resin, including a high-hydroxyl-value resin and a low-hydroxyl-value resin; the high-hydroxyl-value resin has a hydroxyl mass fraction of 3.3%~4.0%, and the low-hydroxyl-value resin has a hydroxyl mass fraction of 0.4~1.0%. The low-hydroxyl-value resin is mainly acrylic resin, and the high-hydroxyl-value resin is polyurethane or acrylic resin. The high-hydroxyl-value resin provides high crosslinking density and film fullness, while the low-hydroxyl-value resin provides adhesion and flexibility. The combination of the two allows the coating film to maintain a high crosslinking density while also taking into account good flexibility and adhesion, resulting in comprehensive mechanical properties superior to a single resin system.

[0015] As a further preferred embodiment of the above technical solution, the mass ratio of the high hydroxyl value resin to the low hydroxyl value resin is (2:5) to (3:4).

[0016] As a further preferred embodiment of the above technical solution, component A further includes 3-5 parts by weight of matting powder; the matting powder is high-permeability silica. High-permeability silica can retain the permeability of the paint film as much as possible, and the presence of matting powder will prolong the sealing time of the paint film surface, facilitating the escape of gases carried in the internal pores and cracks of the magnesium alloy material after coating, avoiding the possibility of bubbles or through-holes in the paint film, and enhancing the paint film's ability to resist external erosion.

[0017] As a further preferred embodiment of the above technical solution, component A further includes additives, which include 0.6 to 1 parts by weight of a wetting agent, 0.3 to 0.5 parts by weight of an antifoaming agent, 0.05 to 0.1 parts by weight of a pH adjuster, and 0.2 to 0.4 parts by weight of a thickener.

[0018] As a further preferred embodiment of the above technical solution, component A comprises the following components in parts by weight: 45-75 parts water-based resin, 3-5 parts epoxy phosphate, 3-5 parts sulfonate corrosion inhibitor, 0.6-1 part wetting agent, 0.3-0.5 parts defoamer, 3-6 parts solvent, 0.05-0.1 parts pH adjuster, 0.2-0.4 parts thickener, 3-5 parts matting powder and 5-8 parts deionized water.

[0019] As a further preferred embodiment of the above technical solution, the matting powder is high-permeability silica. High-permeability silica can retain the permeability of the paint film as much as possible, and the presence of matting powder will prolong the sealing time of the paint film surface, facilitating the escape of gases carried in the internal pores and cracks of the coated magnesium alloy material, avoiding the possibility of bubbles or through-holes in the paint film, and enhancing the paint film's ability to resist external erosion.

[0020] As a further preferred embodiment of the above technical solution, component A comprises the following components in parts by weight: 45-75 parts water-based resin, 3-5 parts epoxy phosphate, 3-5 parts sulfonate corrosion inhibitor, 0.6-1 part wetting agent, 0.3-0.5 parts defoamer, 3-6 parts solvent, 0.05-0.1 part pH adjuster, 0.2-0.4 parts thickener, 3-5 parts matting powder, and 5-8 parts deionized water; Component B comprises 70-80 parts by weight of curing agent and 20-30 parts by weight of solvent.

[0021] Further enhance the bonding strength between the coating and the magnesium alloy substrate.

[0022] As a further preferred embodiment of the above technical solution, in component A, the solvent includes at least one of diethylene glycol butyl ether, dipropylene glycol butyl ether, and decyl alcohol ester; in component B, the solvent includes at least one of propylene glycol methyl ether acetate and propylene glycol diacetate. The solvent selected in component A has a relatively slow evaporation rate, which is beneficial for the overflow of air bubbles in the paint film after spraying and avoids the formation of micropores after the paint film dries.

[0023] As a further preferred embodiment of the above technical solution, it also includes component C, which includes a silane coupling agent, and the mass ratio of component A, component B and component C is 100:(10~15):(2~4).

[0024] Silane coupling agents possess the potential to react with both inorganic MAO films and organic resins, while nano-SiO2 and Al2O3 simultaneously improve pore filling, coating hardness, and media diffusion pathways. The silane coupling agent exists as an independent component, prepared and used immediately during application, isolating it from water in component A to prevent hydrolysis and fully leveraging its interface-enhancing effect on magnesium alloy substrates.

[0025] Based on the same technical concept, the present invention also provides a method for preparing the water-based magnesium alloy anti-corrosion coating described above, characterized in that component A is prepared by the following steps: Component A is prepared using the following steps: S1. Mix the water-based resin, wetting agent and defoamer thoroughly to obtain solution A; S2. Dissolve epoxy phosphate in a solvent to obtain solution B. Adjust solution B to weak alkalinity using a pH adjuster. Slowly add solution B to solution A and mix thoroughly to obtain solution C. S3. Slowly add the abrasive powder to solution C, stir and disperse evenly, and grind to a suitable fineness to obtain a slurry; S4. Add sulfonate corrosion inhibitor, thickener and deionized water to the slurry to obtain component A.

[0026] Water-based magnesium alloy anti-corrosion coating is obtained by mixing components A, B, and C in the specified mass ratio.

[0027] Based on the same technical concept, the present invention also provides an application of the water-based magnesium alloy anti-corrosion coating described above in the corrosion protection of magnesium alloy substrates in the field of 3C consumer electronics, wherein the water-based magnesium alloy anti-corrosion coating is used to form an anti-corrosion coating on the surface of the magnesium alloy substrate.

[0028] As a further preferred embodiment of the above technical solution, the water-based magnesium alloy anti-corrosion coating is used to form an anti-corrosion coating on the surface of magnesium alloy that has been treated with MAO or has a thin layer of MAO on its surface.

[0029] As a further preferred embodiment of the above technical solution, the anti-corrosion coating formed by the water-based magnesium alloy anti-corrosion coating has a film thickness of 20~25μm.

[0030] Compared with the prior art, the present invention has the following beneficial effects: (1) The water-based magnesium alloy anti-corrosion coating of the present invention can form a corrosion-resistant coating with strong adhesion and balanced mechanical properties on magnesium alloy metal, and effectively protect the magnesium alloy substrate. It adopts the combination of epoxy phosphate ester and sulfonate corrosion inhibitor, and the synergistic effect of the two can effectively enhance the corrosion resistance of the magnesium alloy substrate, especially the corrosion resistance under specific environments such as long-term high temperature and high humidity, acid, and chemicals.

[0031] (2) The present invention uses a specific matte powder formulation to avoid the formation of pores and interconnected pores caused by air bubbles escaping from the gaps in the magnesium alloy material, thus preventing the protective effect of the paint film from failing. The solvent type and ratio selected in this invention patent also facilitate the escape of air bubbles during the paint film drying process, preventing the formation of a porous structure after the paint film dries. The present invention avoids the use of rust-inhibiting fillers to achieve the anti-corrosion performance of the paint film, and well preserves the permeability of the paint film.

[0032] (3) The water-based magnesium alloy anti-corrosion coating of the present invention has a simple preparation process and is easy to operate. It does not require complicated equipment and is suitable for large-scale industrial production. It is a three-component system (A, B, C), which can be mixed in proportion when used. The construction activation period is moderate and the operation window is wide, making it suitable for a variety of coating processes.

[0033] (4) The coating of this invention is specifically designed for magnesium alloy substrates in the 3C consumer electronics field. It can effectively resist long-term corrosion from human sweat and salt spray environments, and is suitable for surface protection of magnesium alloy structural parts such as laptops, tablets, smartphones, camera bodies, drones, and smart wearable devices. Unlike ordinary anti-corrosion coatings, the coating of this invention, through the reasonable combination of rust inhibitors and matting powder, greatly preserves the transparency of the paint film, and can better present the metallic texture of the material, especially the texture and anti-corrosion requirements of magnesium alloy materials with MAO thin layers. It meets the high requirements of 3C consumer electronics products for appearance, and can be applied by spraying and other methods. It has good adaptability to substrates and can be used for coating complex shaped structural parts such as magnesium alloy die castings, and has good prospects for industrial application. Detailed Implementation

[0034] The technical solution of the present invention will be further explained and described below with reference to specific embodiments.

[0035] In each embodiment, the high hydroxyl resin used is one or both of the following: Covestro's U2750 product (hydroxyl mass fraction of approximately 3.6%) and Wanhua Chemical Group Co., Ltd.'s 2702 product (hydroxyl mass fraction of approximately 3.9%).

[0036] The low-hydroxyl resins used are one or more of the following: WDP-047D (hydroxyl mass fraction approximately 0.4%) produced by Guangzhou Xinyingyuan Materials Co., Ltd.; RS 8257 (hydroxyl mass fraction approximately 0.5%) produced by Guangdong Ruishi New Materials Technology Co., Ltd.; and 299 (hydroxyl mass fraction approximately 0.9%) produced by Guangdong Baohui New Materials Technology Co., Ltd.

[0037] The wetting agent used is at least one of the following products manufactured by Evonik Industries: Twin 4100, WET 270, and WET 280.

[0038] The defoamer used is BYK-024, manufactured by BYK Chemicals, and at least one of Tego 825 and Tego 845, manufactured by Evonik Industries.

[0039] The sulfonate corrosion inhibitors used are one or both of the following: COR AM 35B produced by Xianchuang Chemical and NACORR 1652 produced by King Industries.

[0040] The epoxy phosphate used is one or both of the following: product No. 25046 produced by Longhai Chemical Co., Ltd., and product No. 2063 produced by Lubrizol.

[0041] The matting powder used is at least one of the following: Evonik Industries' TS-100 product and Grace's ED 80 product.

[0042] The pH adjuster used is at least one of N,N-dimethylethanolamine (DMEA) and 2-amino-2-methyl-1-propanol (AMP-95).

[0043] The thickeners used are at least one of the following: Hemings Corporation's products with brand names 299 and FX1010, and Evonik Industries' product with brand name Tego 3060.

[0044] The curing agent used is at least one of the grades XP2487 / 1 and XP2655 manufactured by Covestro AG.

[0045] The silane coupling agents used are at least one of the following: GLYMO, manufactured by Evonik Industries; MP-200, manufactured by Momentive Advanced Materials; and KH-560.

[0046] Example 1: The composition of the water-based magnesium alloy anti-corrosion coating in this embodiment is shown in Table 1. The preparation method of component A is as follows: (1) Mix 20 parts of U2750, 50 parts of WDP-047D, 0.6 parts of Twin4100 and 0.3 parts of BYK-024 at 800 RPM for 15 minutes to obtain a mixed solution; (2) Dissolve 3 parts of Longhai Chemical 25046 in 3 parts of diethylene glycol butyl ether, then adjust to weak alkalinity with 0.05 parts of DMEA, and slowly add it to the mixed solution and mix it evenly with other components to obtain a mixed system; (3) Slowly add 3 parts of TS-100 matting powder to the mixing system, increase the speed to 1200 RPM, stir for 15 minutes, and then use a grinder to grind the fineness to 25 microns to obtain the mixed slurry; (4) Add 3 parts of COR AM 35B, 0.2 parts of R299 and 5 parts of deionized water to the mixed slurry to obtain component A.

[0047] The preparation method of component B is as follows: 70 parts of 2487 / 1 and 30 parts of propylene glycol methyl ether acetate are thoroughly mixed.

[0048] Mix 100 parts by weight of component A, 10 parts by weight of component B and 2 parts by weight of component C (silane coupling agent GLYMO) in the specified proportions, spray the mixture onto the magnesium alloy material, let it stand at room temperature for 3 minutes, and then bake it at 70°C to obtain a magnesium alloy anti-corrosion coating.

[0049] Example 2: The composition of the water-based magnesium alloy anti-corrosion coating in this embodiment is shown in Table 1. The preparation method is basically the same as that in Example 1, except that the stirring time in step (3) of component A preparation is 17 min.

[0050] Mix 100 parts by weight of component A, 12 parts by weight of component B and 3 parts by weight of component C (silane coupling agent MP200) in the specified proportions, spray the mixture onto the magnesium alloy material, let it stand at room temperature for 4 minutes, and then bake it at 75°C to obtain a magnesium alloy anti-corrosion coating.

[0051] Example 3: The composition of the water-based magnesium alloy anti-corrosion coating in this embodiment is shown in Table 1. The preparation method is basically the same as that in Example 1. The only difference is that the mixing speed in step (1) of component A preparation is 900 RPM and the mixing time is 18 min, and the stirring time in step (3) is 20 min.

[0052] Mix 100 parts by weight of component A, 15 parts by weight of component B and 3 parts by weight of component C (silane coupling agent KH-560) in the specified proportions, spray the mixture onto the magnesium alloy material, let it stand at room temperature for 5 minutes, and then bake it at 80°C to obtain a magnesium alloy anti-corrosion coating.

[0053] Example 4: The composition of the water-based magnesium alloy anti-corrosion coating in this embodiment is shown in Table 1. The preparation method is basically the same as that in Example 1. The only difference is that the mixing speed in step (1) of component A preparation is 1000 RPM and the mixing time is 20 min, and the stirring time in step (3) is 25 min.

[0054] Mix 100 parts by weight of component A, 15 parts by weight of component B and 4 parts by weight of component C (2 parts of silane coupling agent GLYMO and 2 parts of KH-560) in the specified proportions, spray the mixture onto the magnesium alloy material, let it stand at room temperature for 5 minutes, and then bake it at 80°C to obtain a magnesium alloy anti-corrosion coating.

[0055] Comparative Example 1: The composition of the water-based magnesium alloy anti-corrosion coating in this comparative example is shown in Table 1, and the preparation method is the same as that in Example 1.

[0056] Mix 100 parts by weight of component A, 10 parts by weight of component B and 2 parts by weight of component C (silane coupling agent GLYMO) in the specified proportions, spray the mixture onto the magnesium alloy material, let it stand at room temperature for 3 minutes, and then bake it at 70°C to obtain a magnesium alloy anti-corrosion coating.

[0057] Comparative Example 2: The composition of the water-based magnesium alloy anti-corrosion coating in this comparative example is shown in Table 1. The preparation method is basically the same as that in Example 1, except that no sulfonate corrosion inhibitor component is added to component A.

[0058] Mix 100 parts by weight of component A, 10 parts by weight of component B and 2 parts by weight of component C (silane coupling agent GLYMO) in the specified proportions, spray the mixture onto the magnesium alloy material, let it stand at room temperature for 3 minutes, and then bake it at 70°C to obtain a magnesium alloy anti-corrosion coating.

[0059] Comparative Example 3: The composition of the water-based magnesium alloy anti-corrosion coating in this comparative example is shown in Table 1. The preparation method is basically the same as that in Example 1.

[0060] Mix 100 parts by weight of component A, 10 parts by weight of component B and 2 parts by weight of component C (silane coupling agent GLYMO) in the specified proportions, spray the mixture onto the magnesium alloy material, let it stand at room temperature for 3 minutes, and then bake it at 70°C to obtain a magnesium alloy anti-corrosion coating.

[0061] Comparative Example 4: The composition of the water-based magnesium alloy anti-corrosion coating in this comparative example is shown in Table 1. The preparation method is basically the same as that in Example 1.

[0062] Mix 100 parts by weight of component A, 10 parts by weight of component B and 2 parts by weight of component C (silane coupling agent GLYMO) in the specified proportions, spray the mixture onto the magnesium alloy material, let it stand at room temperature for 3 minutes, and then bake it at 70°C to obtain a magnesium alloy anti-corrosion coating.

[0063] The performance of the magnesium alloy anti-corrosion coatings in each embodiment and comparative example was tested, and the results are shown in Table 2.

[0064] Table 1: Component proportions of magnesium alloy anti-corrosion coatings in various examples and comparative examples

[0065] Table 2: Performance test results of magnesium alloy anti-corrosion coatings in each embodiment and comparative example

[0066] The above embodiments are only used to illustrate the technical solutions disclosed in this invention, and are not intended to limit it. Although the invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions disclosed in the embodiments of this invention, and should all be included within the protection scope disclosed in this invention.

Claims

1. A water-based anti-corrosion coating for magnesium alloys, characterized in that, Includes component A and component B; Component A includes a resin matrix, epoxy phosphate, sulfonate corrosion inhibitor and solvent; the mass ratio of epoxy phosphate and sulfonate corrosion inhibitor is (0.8:1) to (1:1); Component B includes a curing agent.

2. The water-based magnesium alloy anti-corrosion coating according to claim 1, characterized in that, The mass ratio of component A to component B is 100:(10~15); Component A comprises the following components in parts by weight: 45-75 parts resin matrix, 3-5 parts epoxy phosphate ester, 3-5 parts sulfonate corrosion inhibitor and solvent; Component B includes a solvent and 70-80 parts by weight of a curing agent, wherein the curing agent is a hexamethylene diisocyanate polymer.

3. The water-based magnesium alloy anti-corrosion coating according to claim 1, characterized in that, The resin matrix includes high hydroxyl value resin and low hydroxyl value resin; the high hydroxyl value resin has a hydroxyl mass fraction of 3.3% to 4.0%, and the low hydroxyl value resin has a hydroxyl mass fraction of 0.4% to 1.0%.

4. The water-based magnesium alloy anti-corrosion coating according to claim 3, characterized in that, The mass ratio of the high hydroxyl value resin to the low hydroxyl value resin is (2:5) to (3:4).

5. The water-based magnesium alloy anti-corrosion coating according to claims 1-4, characterized in that, Component A also includes 3 to 5 parts by weight of matting powder.

6. The water-based magnesium alloy anti-corrosion coating according to any one of claims 1-4, characterized in that, Component A further includes additives, which include 0.6 to 1 part by weight of a wetting agent, 0.3 to 0.5 parts by weight of an antifoaming agent, 0.05 to 0.1 parts by weight of a pH adjuster, and 0.2 to 0.4 parts by weight of a thickener.

7. The water-based magnesium alloy anti-corrosion coating according to any one of claims 1-4, characterized in that, It also includes component C, which comprises a silane coupling agent; the mass ratio of component A, component B and component C is 100:(10~15):(2~4).

8. A method for preparing a water-based magnesium alloy anti-corrosion coating according to any one of claims 1-7, characterized in that, Component A is prepared using the following steps: S1. Thoroughly stir the water-based resin, wetting agent, and defoamer to obtain solution A; S2. Dissolve epoxy phosphate in a solvent to obtain solution B. Adjust solution B to weak alkalinity using a pH adjuster. Slowly add solution B to solution A and mix thoroughly to obtain solution C. S3. Slowly add the abrasive powder to solution C, stir and disperse evenly, and grind to a suitable fineness to obtain a slurry; S4. Add sulfonate corrosion inhibitor, thickener and deionized water to the slurry to obtain component A.

9. The method for preparing the water-based magnesium alloy anti-corrosion coating according to claim 8, characterized in that, In S3, grinding is performed until the fineness of solid particles in the mixed slurry is less than 25 μm.

10. The application of the water-based magnesium alloy anti-corrosion coating according to any one of claims 1-7 in the corrosion protection of magnesium alloy substrates in the field of 3C consumer electronics.

Citation Information

Patent Citations

  • A water-based two-component polyurethane coating and its preparation method and application

    CN115710454B